PENINGKATAN KEMAMPUAN MENULIS TEKS PROSEDUR DENGAN MODEL ACTIVE LEARNING - Sujanti Sujanti (sarasvati, 2020)
Writing is not an ability that can be mastered by itself, but must go through a process of learning and habituation. Writing procedure text is a container that can be used as a habit. Especially in the 2013 curriculum, procedure text is mandatory material that must be studied in grade VII SMP students. Based on observations during online learning in the midst of the Covid 19 pandemic at SMP Mutiara 4 Bandung, students find it difficult to learn. expressing ideas and ideas in written form, because the learning models and media used by the teacher are not attractive so that learning feels boring and unpleasant. Based on the descriptions presented above, the authors are interested in conducting Classroom Action Research (CAR) with a model. Acitive Learning through gamabar media. This classroom action research was carried out in two cycles, each of which contained four components, namely planning, implementing, observing and reflecting. The results showed that the application of the active learning model through image media could improve the ability to write procedural texts. The application of the Active Learning learning model through image media is more effective, it is proven that students are more active and more creative in developing writing and are able to improve the quality of students' writing as evidenced by an increase in the results of the average score in cycle I (62,) and the acquisition of average scores cycle II (78,6), so there is a difference in the average value (16,). Based on the research results, it can be concluded that the active learning model through image media is effective in learning to write procedural texts.